Carbon fiber reinforced composite material and method for manufacturing carbon fiber reinforced composite material

JP7917449B2Active Publication Date: 2026-09-08SEKISUI CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022563153
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-24
Filing Date
2022-09-22
Publication Date
2026-09-08
Estimated Expiration
2042-09-22

AI Technical Summary

Benefits of technology

【0069】 本発明によれば、優れたタック性、エポキシ樹脂との相溶性及び界面密着性を有するとともに、高い機械的強度を実現することが可能な炭素繊維強化複合材料及び炭素繊維強化複合材料の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007917449000001
    Figure 0007917449000001
  • Figure 0007917449000002
    Figure 0007917449000002
  • Figure 0007917449000003
    Figure 0007917449000003
Patent Text Reader

Abstract

The present invention provides: a carbon-fiber-reinforced composite material having exceptional tackiness as well as compatibility and interfacial adhesiveness with epoxy resins, the carbon-fiber-reinforced composite material being capable of realizing high mechanical strength; and a method for producing a carbon-fiber-reinforced composite material. The present invention is a carbon-fiber-reinforced composite material containing carbon fibers, an epoxy resin, a curing agent, and a polyvinyl acetal resin, wherein the polyvinyl acetal resin contains structural units represented by formula (1), and R1 in formula (1) is a C1 or higher alkyl group. In formula (1), R1 may be the same or different.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to carbon fiber reinforced composite materials and methods for producing carbon fiber reinforced composite materials. [Background technology]

[0002] Fiber-reinforced plastics, a type of fiber-reinforced composite material, are lightweight, high-strength, and highly rigid, making them widely used in applications ranging from structural materials for aircraft, automobiles, and ships to general-purpose sports equipment such as tennis rackets, fishing rods, and golf club shafts. One method of manufacturing fiber-reinforced plastics involves using a prepreg, an intermediate material made by impregnating a reinforcing material consisting of long fibers (continuous fibers) such as reinforcing fibers with a matrix resin. This method has the advantage of making it easier to control the reinforcing fiber content of the fiber-reinforced plastic and allowing for the design of a higher reinforcing fiber content.

[0003] Epoxy resins are preferably used as the matrix resin for such fiber-reinforced composite materials due to their excellent moldability. Because epoxy resins are used, fiber-reinforced composite materials with excellent mechanical properties and heat resistance are obtained even after curing, and thus they are used in a wide range of industrial fields.

[0004] For example, Patent Document 1 describes a prepreg containing a predetermined amount of reinforcing fiber, epoxy resin, carboxyl group-containing polyvinyl formal resin, and amine curing agent. Furthermore, Patent Document 2 describes a prepreg for fiber-reinforced composite materials containing a predetermined amount of epoxy resin, a thermoplastic resin soluble in epoxy resin, and a latent curing agent. Furthermore, Patent Document 3 describes a prepreg obtained by impregnating reinforcing fibers with an epoxy resin composition containing an epoxy compound, a curing agent, and a polyvinyl acetal resin. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] International Publication No. 2019 / 202762 [Patent Document 2] Japanese Unexamined Patent Publication No. Hei 6-9802 [Patent Document 3] Japanese Unexamined Patent Publication No. Hei 5-186667 [Summary of the Invention] [Problem to be Solved by the Invention]

[0006] However, even when the techniques described in Patent Documents 1 to 3 are used, there is a problem that the resulting prepreg has insufficient tackiness (surface adhesiveness), leading to reduced handleability. Additionally, the resulting prepreg has a problem that the interfacial adhesion between the reinforcing fibers and the matrix resin is poor, and sufficient performance cannot be obtained. Furthermore, there is a problem that the toughness of the resulting prepreg is insufficient, resulting in decreased mechanical strength.

[0007] In view of the above situation, an object of the present invention is to provide a carbon fiber-reinforced composite material that has excellent tackiness, compatibility with epoxy resins, and interfacial adhesion, and can achieve high mechanical strength, as well as a method for producing the carbon fiber-reinforced composite material. [Means for Solving the Problem]

[0008] The present disclosure (1) is a carbon fiber-reinforced composite material containing carbon fibers, an epoxy resin, a curing agent, and a polyvinyl acetal resin, wherein the polyvinyl acetal resin contains a constitutional unit represented by the following formula (1), and R in the following formula (1) 1 is an alkyl group having 1 or more carbon atoms. This is the carbon fiber-reinforced composite material.

[0009] [Chemical Formula] In formula (1), R 1 may be the same or may be different from each other. This disclosure (2) states that polyvinyl acetal resin is R in formula (1). 1 However, the carbon fiber reinforced composite material is the one described in disclosure (1), wherein the alkyl group has 1 or more carbon atoms, and / or the alkyl group has 3 or more carbon atoms. Disclosure (3) is a carbon fiber reinforced composite material according to Disclosure (1) or (2), wherein the polyvinyl acetal resin has a hydroxyl group content of 15.0 mol% or more and 45.0 mol% or less. Disclosure (4) is a carbon fiber reinforced composite material according to any one of Disclosures (1) to (3), wherein the polyvinyl acetal resin has an average degree of polymerization of 2500 or less. Disclosure (5) is a carbon fiber reinforced composite material according to any of Disclosures (1) to (4), wherein the polyvinyl acetal resin has a glass transition temperature of 75°C or higher. Disclosure (6) is a carbon fiber reinforced composite material according to any one of Disclosures (1) to (5), wherein the polyvinyl acetal resin contains constituent units having acid-modified groups. Disclosure (7) is a carbon fiber reinforced composite material according to Disclosure (6), wherein the polyvinyl acetal resin has a content of 0.01 to 20 mol% of constituent units having acid-modified groups. Disclosure (8) is a carbon fiber reinforced composite material according to any of Disclosures (1) to (7), wherein the polyvinyl acetal resin has a hydroxyl group content of 16.0 mol% or more and 45.0 mol% or less. Disclosure (9) is a carbon fiber reinforced composite material according to any of Disclosures (1) to (8), wherein the polyvinyl acetal resin content is 0.01 parts by weight or more and 40.0 parts by weight or less per 100 parts by weight of epoxy resin. The present disclosure (10) comprises at least the steps of: preparing a resin composition containing an epoxy resin, a curing agent, and a polyvinyl acetal resin; and compounding the resin composition with carbon fibers, wherein the polyvinyl acetal resin contains the constituent units shown in the following formula (1), and R in the following formula (1) 1 This is a method for producing a carbon fiber reinforced composite material in which is an alkyl group having 1 or more carbon atoms. The present invention will be described in detail below.

[0010] As a result of intensive studies, the present inventors have found that a carbon fiber reinforced composite material containing a polyvinyl acetal resin having a predetermined structure has excellent tackiness, compatibility with epoxy resins and interfacial adhesion, and can achieve high mechanical strength, and have accomplished the present invention.

[0011] The carbon fiber reinforced composite material of the present invention contains a polyvinyl acetal resin. The polyvinyl acetal resin contains a structural unit represented by the following formula (1), wherein R in the following formula (1) 1 is an alkyl group having 1 or more carbon atoms.

[0012]

Chemical Formula

[0013] In the above formula (1), R 1 is an alkyl group having 1 or more carbon atoms. When the alkyl group has 1 or more carbon atoms, the toughness of the carbon fiber composite material is improved, which provides the advantage of excellent impact resistance. The number of carbon atoms is preferably 1 or more, and more preferably 6 or less. In particular, R in formula (1) 1 is preferably an alkyl group having 1 or more carbon atoms and / or an alkyl group having 3 or more carbon atoms.

[0014] The above R 1 may be the same, or may be a combination of different groups. The above R 1 when being a combination of different groups, is preferably a combination of an alkyl group having 1 or more carbon atoms and an alkyl group having 3 or more carbon atoms.

[0015] The alkyl group mentioned above is not particularly limited as long as it has one or more carbon atoms, and examples include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, iso-butyl group, sec-butyl group, tert-butyl group, etc. Other examples include pentyl group, hexyl group, heptyl group, 2-ethylhexyl group, octyl group, nonyl group, decyl group, undecyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, octadecyl group, etc. Among these, methyl group and n-propyl group are preferred.

[0016] In the above polyvinyl acetal resin, the preferred lower limit of the content of constituent units having an acetal group represented by the above general formula (1) (hereinafter also referred to as "alkyl acetal group content") is 30 mol%, and the preferred upper limit is 85 mol%. If the amount of alkyl acetal groups is 30 mol% or more, a polyvinyl acetal resin with excellent toughness can be obtained. If the amount of acetal groups is 85 mol% or less, compatibility with epoxy resins can be improved. The amount of alkyl acetal group described above has a more preferable lower limit of 60 mol% and a more preferable upper limit of 80 mol%. In this specification, the method for calculating the amount of alkyl acetal groups is to count the number of alkyl acetal units having two hydroxyl groups, since the acetal groups of polyvinyl acetal resin are obtained by acetalizing structural units having two hydroxyl groups of polyvinyl alcohol resin.

[0017] In the above polyvinyl acetal resin, R in the above general formula (1) 1 When the compound has a methyl group, the preferred lower limit of the content of the constituent unit (hereinafter also referred to as the "degree of acetalization") is 5 mol%, and the preferred upper limit is 85 mol%. By keeping it within the above range, compatibility with epoxy resins can be maintained, and excellent viscosity properties can be obtained. Furthermore, in the above polyvinyl acetal resin, R in the above general formula (1) 1When the compound has an n-propyl group, the preferred lower limit of the content of this constituent unit (hereinafter also referred to as the "degree of butyralization") is 0.1 mol%, and the preferred upper limit is 80 mol%. By keeping it within the above range, compatibility with epoxy resins can be maintained, and excellent viscosity properties can be obtained. In the above polyvinyl acetal resin, R in the above general formula (1) 1 When the compound has both a methyl group and an n-propyl group, the ratio of the degree of acetalization to the degree of butyralization [degree of acetalization / degree of butyralization] is preferably 0.06 or more and 850 or less. Furthermore, the ratio is more preferably 0.1 or more and 375 or less.

[0018] [ka]

[0019] In the above polyvinyl acetal resin, the preferred lower limit of the content of constituent units having hydroxyl groups represented by the above general formula (2) (hereinafter also referred to as "hydroxyl group content") is 15.0 mol%, and the preferred upper limit is 45.0 mol%. When the amount of hydroxyl groups is 15.0 mol% or more, a polyvinyl acetal resin with excellent adhesive properties can be obtained. When the amount of hydroxyl groups is 45.0 mol% or less, the compatibility with epoxy resin can be sufficiently improved. The above hydroxyl group content has a more preferable lower limit of 16.0 mol%, an even more preferable lower limit of 18.0 mol%, an even more preferable lower limit of 20.0 mol%, a more preferable upper limit of 40.0 mol%, and an even more preferable upper limit of 38.0 mol%.

[0020] In the polyvinyl acetal resin described above, the preferred lower limit of the content of constituent units having an acetyl group represented by the general formula (3) above (hereinafter also referred to as "acetyl group content") is 0.1 mol%, and the preferred upper limit is 25 mol%. When the amount of acetyl groups is 0.1 mol% or more, it is possible to suppress the increase in viscosity due to intramolecular and intermolecular hydrogen bonding of hydroxyl groups in the polyvinyl acetal resin. When the amount of acetyl groups is 25 mol% or less, it is possible to improve the handling properties without excessively reducing the heat resistance of the polyvinyl acetal resin. The above acetyl group content has a more preferable lower limit of 0.5 mol%, a more preferable upper limit of 15 mol%, an even more preferable lower limit of 0.8 mol%, and an even more preferable upper limit of 14 mol%. In the above polyvinyl acetal resin, the total amount of alkyl acetal groups, hydroxyl groups, and acetyl groups is preferably greater than 95 mol%, and more preferably 96 mol% or more.

[0021] The above polyvinyl acetal resin preferably contains constituent units having acid-modified groups. The presence of the above-mentioned acid-modified group in the constituent unit improves compatibility with epoxy resins, thereby enhancing the toughness of the resulting carbon fiber reinforced composite material. Furthermore, improved adhesion to carbon fibers suppresses delamination between the matrix resin and carbon fibers in the carbon fiber reinforced composite material. This contributes to reducing defects and improving mechanical strength.

[0022] Examples of the acid-modified groups mentioned above include carboxyl groups, sulfonic acid groups, maleic acid groups, sulfinic acid groups, sulfenic acid groups, phosphate groups, phosphonic acid groups, and salts thereof.

[0023] The constituent unit having the above-mentioned acid-modifying group may have a structure in which two acid-modifying groups are bonded to the same carbon atom constituting the main chain, or it may have a structure in which one acid-modifying group is bonded to the carbon atom constituting the main chain. Furthermore, the acid-modified group may be directly bonded to the carbon atoms constituting the main chain, or it may be bonded to the carbon atoms constituting the main chain via a linking group such as an alkylene group. Furthermore, the above-mentioned acid-modified group may also have a structure in which the acid-modified group is bonded to the carbon that constitutes the acetal group. When the above-mentioned structural unit having the acid-modified group has a structure in which the acid-modified group is bonded to a carbon constituting the main chain via an alkylene group, the alkylene group is preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 1 to 5 carbon atoms, and even more preferably an alkylene group having 1 to 3 carbon atoms.

[0024] Examples of alkylene groups having 1 to 10 carbon atoms include linear alkylene groups, branched alkylene groups, and cyclic alkylene groups. Examples of the linear alkylene groups mentioned above include methylene groups, vinylene groups, n-propylene groups, tetramethylene groups, pentamethylene groups, hexamethylene groups, octamethylene groups, decamethylene groups, and the like. Examples of the branched alkylene groups mentioned above include methylmethylene group, methylethylene group, 1-methylpentylene group, and 1,4-dimethylbutylene group. Examples of the above-mentioned cyclic alkylene groups include cyclopropylene, cyclobutylene, and cyclohexylene. Among these, linear alkylene groups are preferred, methylene groups, vinylene groups, and n-propylene groups are more preferred, and methylene groups and vinylene groups are even more preferred.

[0025] When the acid-modified group is a carboxyl group, examples of constituent units containing the carboxyl group include the constituent unit represented by the following formula (4-1), the constituent unit represented by the following formula (4-2), the constituent unit represented by the following formula (4-3), and so on.

[0026] [ka]

[0027] In the above equation (4-1), R 2 and R 3 Each is independently an alkylene group with 0 to 10 carbon atoms, X 1 and X 2 Each of these independently represents a hydrogen atom, a metal atom, or a methyl group. In formula (4-2) above, R 4 , R5 and R 6 Each is independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, R 7 X is an alkylene group with 0 to 10 carbon atoms. 3 R represents a hydrogen atom, a metal atom, or a methyl group. 2 , R 3 or R 7 The fact that R is an alkylene group with 0 carbon atoms means that 2 , R 3 or R 7 This means that it is a single bond. In equation (4-3) above, R 8 X is an alkylene group with 0 to 10 carbon atoms. 4 represents a hydrogen atom, a metal atom, or a methyl group. Note that a carbon number of 0 means that there is no alkylene group present, that is, it means that there is no alkylene group and it is directly bonded.

[0028] The above X 1 and X 2 If at least one of these is a metal atom, examples of such metal atoms include sodium atoms, lithium atoms, potassium atoms, etc. Among these, sodium atoms are preferred.

[0029] The above polyvinyl acetal resin preferably has a structural unit represented by the above formula (4-1). When the polyvinyl acetal resin has a structural unit represented by the above formula (4-1), its compatibility with epoxy resin can be improved.

[0030] The above X 3 If X is a metal atom, examples of such metal atoms include sodium atoms, lithium atoms, potassium atoms, etc. Among these, sodium atoms are preferred. 4 The same applies when it is a metal atom.

[0031] The above polyvinyl acetal resin has a preferred lower limit of 0.01 mol% and a preferred upper limit of 20 mol% for the content of constituent units having acid-modified groups (hereinafter also referred to as "amount of acid-modified groups"). When the amount of acid-modified groups is 0.01 mol% or more, the effects of the polyvinyl acetal resin having acid-modified groups can be fully exhibited, and the adhesion of the resulting carbon fiber reinforced composite material can be further improved. When the amount of acid-modified groups is 20 mol% or less, the tackiness and toughness of the carbon fiber reinforced composite material can be further improved. A more preferable lower limit for the amount of acid-modified groups in the polyvinyl acetal resin is 0.05 mol%, a more preferable upper limit is 15 mol%, an even more preferable lower limit is 0.1 mol%, and an even more preferable upper limit is 10 mol%. In this specification, the amount of acid-modified groups in polyvinyl acetal resin refers to the proportion of constituent units having acid-modified groups to the total constituent units of the polyvinyl acetal resin.

[0032] The above polyvinyl acetal resin preferably has an average degree of polymerization of 2500 or less. A minimum average degree of polymerization of 2500 provides sufficient mechanical strength. Furthermore, a minimum average degree of polymerization of 1000 significantly improves solubility in organic solvents, resulting in superior coating properties and dispersibility. The more preferable lower limit for the average degree of polymerization is 150, and the more preferable upper limit is 1000. The average degree of polymerization mentioned above is the same as the average degree of polymerization of the raw polyvinyl alcohol resin. The average degree of polymerization of the raw polyvinyl alcohol resin can be measured in accordance with JIS K6726-1994.

[0033] The polyvinyl acetal resin described above preferably has a glass transition temperature (Tg) of 75°C or higher. A glass transition temperature of 75°C or higher improves heat resistance and reduces the amount of seepage during impregnation. A more preferable lower limit for the glass transition temperature is 80°C. The upper limit for the glass transition temperature is not particularly limited, but is 115°C. The glass transition temperature can be measured using a differential scanning calorimeter (DSC).

[0034] The above polyvinyl acetal resin, when mixed with epoxy resin and heated until melted, has a preferred lower viscosity of 30 Pa·s and a preferred upper viscosity of 1200 Pa·s when measured using a rheometer at 30°C. The mixing weight ratio of the epoxy resin to the polyvinyl acetal resin is 9:1. By keeping the material within the above range, it is possible to maintain appropriate tackiness after impregnation of the carbon fiber, thereby improving handling performance. Furthermore, the polyvinyl acetal resin described above, when mixed with epoxy resin and heated to dissolve, has a preferred lower limit of viscosity of 0.1 Pa·s and a preferred upper limit of 4.5 Pa·s when measured using a rheometer at 90°C. By keeping the viscosity within the above range, the optimal viscosity is achieved during impregnation of carbon fibers, thereby suppressing the occurrence rate of voids. Furthermore, the polyvinyl acetal resin described above has a preferred lower limit of 6.5 and a preferred upper limit of 12000 for the ratio of viscosity at 30°C to viscosity at 90°C (viscosity at 30°C / viscosity at 90°C). By keeping the ratio within this range, it is possible to manufacture a tough carbon fiber reinforced composite material with excellent tackiness and a low void generation rate. The viscosity mentioned above refers to the viscosity at 30°C and 90°C when a sample prepared by adding 10 parts by weight of polyvinyl acetal resin to 90 parts by weight of epoxy resin, heating and melting it at 150°C, and measuring it using a rheometer under conditions such as using a 20 mm parallel plate, cooling rate: 5°C / min, rotation speed: 100 rpm, and gap: 500 μm. Note that the epoxy resin and thermoplastic resin used in the viscosity measurement above refer to the epoxy resin and thermoplastic resin contained in carbon fiber reinforced composite materials.

[0035] In the carbon fiber reinforced composite material of the present invention, the content of the polyvinyl acetal resin is preferably 0.01 parts by weight or more and 40.0 parts by weight or less per 100 parts by weight of epoxy resin. When the content of the polyvinyl acetal resin is within the above range, the mechanical strength of the resulting carbon fiber reinforced composite material can be sufficiently increased. Furthermore, the content of the polyvinyl acetal resin in the carbon fiber reinforced composite material of the present invention is preferably 0.001% by weight or more, and preferably 35% by weight or less, relative to the total composition. When the content of the polyvinyl acetal resin is within the above range, the mechanical strength of the resulting carbon fiber reinforced composite material can be sufficiently increased.

[0036] The above-mentioned polyvinyl acetal resin can usually be produced by acetalizing polyvinyl alcohol resin. The above acetalization method is not particularly limited, and conventionally known methods can be used. For example, methods include adding various aldehydes to an aqueous solution of polyvinyl alcohol resin, an alcohol solution, a water / alcohol mixed solution, or a dimethyl sulfoxide (DMSO) solution in the presence of an acid catalyst. Furthermore, if the polyvinyl acetal resin contains a constituent unit having an acid-modifying group, the manufacturing method may be a method of acetalizing a polyvinyl alcohol resin containing a constituent unit having an acid-modifying group, or it may be a method of acetalizing unmodified polyvinyl alcohol and then modifying it.

[0037] Examples of the above-mentioned aldehydes include linear, branched, cyclically saturated, cyclically unsaturated, or aromatic aldehydes having 1 to 19 carbon atoms. Specifically, examples include formaldehyde, acetaldehyde, propionyl aldehyde, n-butyraldehyde, isobutyraldehyde, tert-butyraldehyde, benzaldehyde, and cyclohexylaldehyde. The above-mentioned aldehydes may be used alone or in combination of two or more. Furthermore, aldehydes other than formaldehyde, cyclically saturated, cyclically unsaturated, or aromatic aldehydes are preferred, and acetaldehyde and n-butyraldehyde are particularly preferred.

[0038] The amount of aldehyde added can be appropriately set according to the amount of acetal groups in the target polyvinyl acetal resin. In particular, a value of 50 mol% to 95 mol%, more preferably 55 mol% to 90 mol%, per 100 mol% of polyvinyl alcohol resin is preferable because it allows the acetalization reaction to proceed efficiently and makes it easier to remove unreacted aldehydes.

[0039] As the polyvinyl alcohol resin mentioned above, conventionally known polyvinyl alcohol resins such as resins produced by saponifying polyvinyl acetate with alkali, acid, ammonia water, etc., can be used. The polyvinyl alcohol resin described above may be fully saponified, but it does not need to be fully saponified as long as there is at least one unit having a double hydroxyl group at the meso or racemo position at least one location in the main chain; a partially saponified polyvinyl alcohol resin may also be used. Furthermore, as the polyvinyl alcohol resin, copolymers of a monomer copolymerizable with vinyl alcohol and vinyl alcohol, such as ethylene-vinyl alcohol copolymer resins and partially saponified ethylene-vinyl alcohol copolymer resins, can also be used. Examples of the polyvinyl acetate resins mentioned above include ethylene-vinyl acetate copolymers.

[0040] The polyvinyl acetal resin constituting the carbon fiber reinforced composite material of the present invention is preferably an acetalized polyvinyl alcohol resin with a degree of saponification of 75 mol% or more. More preferably, the degree of saponification is between 85 mol% and 99.5 mol%.

[0041] Furthermore, the holding time after the reaction is preferably 1.5 hours or more, and more preferably 2 hours or more, although this depends on other conditions. This holding time allows the acetalization reaction to proceed sufficiently. The holding temperature after the reaction is preferably 15°C or higher, and more preferably 20°C or higher. This holding temperature allows the acetalization reaction to proceed sufficiently.

[0042] The above-mentioned polyvinyl alcohol resin typically contains carboxylates, which are basic components generated during saponification. Therefore, it is preferable to wash away or neutralize these carboxylates before use. By washing away or neutralizing the carboxylates, the condensation reaction of aldehydes, which are catalytically reacted under basic conditions, can be effectively suppressed, thereby further reducing the discoloration of the resin. Examples of cleaning methods in the above cleaning process include extracting basic components with a solvent, dissolving the resin in a good solvent and then adding a poor solvent to reprecipitate only the resin, and adding an adsorbent to a solution containing polyvinyl alcohol-based resin to adsorb and remove basic components. Examples of neutralizing agents used in the above neutralization process include mineral acids such as hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid; inorganic acids such as carbonic acid; carboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, and hexanoic acid; aliphatic sulfonic acids such as methanesulfonic acid and ethanesulfonic acid; aromatic sulfonic acids such as benzenesulfonic acid; and phenols such as phenol.

[0043] The carbon fiber reinforced composite material of the present invention contains carbon fibers. Examples of the carbon fibers mentioned above include PAN-based carbon fibers, pitch-based carbon fibers, cellulose-based carbon fibers, and vapor-grown carbon fibers.

[0044] While twisted yarn, untwisted yarn, and untwisted yarn can be used as forms of the carbon fibers mentioned above, in the case of twisted yarn, the orientation of the filaments constituting the carbon fibers is not parallel, which causes a decrease in the mechanical properties of the resulting carbon fiber reinforced composite material. Therefore, untwisted yarn or untwisted yarn, which offers a good balance between the moldability and strength properties of the carbon fiber reinforced composite material, is preferably used. Furthermore, the carbon fibers may be subjected to oxidation treatment to improve adhesion to the matrix resin, and oxygen-containing functional groups may be introduced. As for the oxidation treatment method, gas-phase oxidation, liquid-phase oxidation, and liquid-phase electrolytic oxidation can be used, but liquid-phase electrolytic oxidation is preferred from the viewpoint of high productivity and uniform treatment.

[0045] The carbon fibers described above preferably have a single fiber fineness of 0.2 to 2.0 dtex, and more preferably 0.4 to 1.8 dtex. A single fiber fineness of 0.2 dtex or higher reduces the likelihood of damage to the carbon fibers due to contact with the guide roller during twisting, and also reduces the likelihood of similar damage during the resin composition impregnation process. A single fiber fineness of 2.0 dtex or lower allows the resin composition to be sufficiently impregnated into the carbon fibers, resulting in improved fatigue resistance. For the same reasons as above, the fineness of the carbon fibers is preferably 50 to 1800 tex. The carbon fibers described above preferably have a filament count in a single fiber bundle ranging from 2,500 to 100,000. If the filament count is less than 2,500, the fiber arrangement tends to meander, which can easily lead to a decrease in strength. Also, if the filament count exceeds 100,000, resin impregnation may be difficult during prepreg production or molding. The filament count is more preferably in the range of 2,800 to 80,000.

[0046] The average fiber diameter of the carbon fibers described above is preferably 2 μm or more, more preferably 3 μm or more, preferably 30 μm or less, and more preferably 26 μm or less. The average fiber length of the carbon fibers described above is preferably 2 mm or more, more preferably 4 mm or more, preferably 100 mm or less, and more preferably 80 mm or less. The form of the carbon fiber described above is not particularly limited, but examples include fibrous, woven, knitted, and nonwoven sheet forms. If the above carbon fiber is in sheet form, the basis weight of the fiber is 100g / m². 2 Preferably, it should be 350 g / m² or more. 2 It is more preferable that it be greater than or equal to 1000 g / m². 2 Preferably, it is 650 g / m². 2 The following is more preferable: Furthermore, the density of the above carbon fiber is 1.6 g / cm³. 3 More than 2.0g / cm3 The following is preferable:

[0047] The carbon fiber content in the carbon fiber reinforced composite material of the present invention is preferably 35% by weight or more, and preferably 100% by weight or less. When the carbon fiber content is within the above range, the mechanical strength of the resulting carbon fiber reinforced composite material can be sufficiently increased. Furthermore, the carbon fiber content is preferably 55 to 3685 parts by weight per 100 parts by weight of the epoxy resin.

[0048] The carbon fiber reinforced composite material of the present invention contains an epoxy resin. By including the epoxy resin mentioned above, crosslinking can be achieved by applying energy through heating or other means, thereby realizing high adhesion.

[0049] Examples of the epoxy resins mentioned above include monofunctional epoxy compounds, difunctional epoxy compounds, and polyfunctional epoxy compounds such as trifunctional or more functional epoxy compounds, and it is more preferable that they include monofunctional epoxy compounds and difunctional epoxy compounds.

[0050] Examples of the above monofunctional epoxy compounds include (meth)acrylic acid esters having a glycidyl group, aliphatic epoxy resins, and aromatic epoxy resins. Among these, it is preferable to contain (meth)acrylic acid esters having a glycidyl group. Examples of (meth)acrylic acid esters having the above-mentioned glycidyl group include glycidyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate glycidyl ether, 2-hydroxypropyl (meth)acrylate glycidyl ether, 3-hydroxypropyl (meth)acrylate glycidyl ether, 4-hydroxybutyl (meth)acrylate glycidyl ether, polyethylene glycol-polypropylene glycol (meth)acrylate glycidyl ether, and the like. Examples of the above-mentioned aliphatic epoxy resins include glycidyl ethers of aliphatic alcohols such as butyl glycidyl ether and lauryl glycidyl ether. Examples of the above-mentioned aromatic epoxy resins include phenylglycidyl ether and 4-t-butylphenylglycidyl ether. Among these, (meth)acrylic acid esters having a glycidyl group and aromatic epoxy resins are preferred.

[0051] Examples of the above-mentioned bifunctional epoxy compounds include bifunctional aromatic epoxy resins such as phenol novolac type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, alkylphenol type epoxy resins, resorcinol type epoxy resins, and bifunctional naphthalene type epoxy resins; bifunctional alicyclic epoxy resins such as dicyclopentadiene dimethanol diglycidyl ethers; polyalkylene glycol diglycidyl ethers such as polypropylene glycol diglycidyl ethers and polyethylene glycol diglycidyl ethers; bifunctional glycidyl ester type epoxy resins such as diglycidyl phthalate, diglycidyl tetrahydrophthalate, and diglycidyl dimer acid diglycidyl esters; bifunctional glycidylamine type epoxy resins such as diglycidylaniline and diglycidyl toluidine; bifunctional heterocyclic epoxy resins; and bifunctional Examples include diarylsulfone-type epoxy resins, hydroquinone-type epoxy resins such as hydroquinone diglycidyl ether, 2,5-di-tert-butylhydroquinone diglycidyl ether, and resorcinol diglycidyl ether; difunctional alkylene glycidyl ether compounds such as butanediol diglycidyl ether, butenediol diglycidyl ether, and butinediol diglycidyl ether; difunctional glycidyl group-containing hydantoin compounds such as 1,3-diglycidyl-5,5-dialkylhydantoin and 1-glycidyl-3-(glycidoxyalkyl)-5,5-dialkylhydantoin; difunctional glycidyl group-containing siloxanes such as 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane and α,β-bis(3-glycidoxypropyl)polydimethylsiloxane; neopentyl glycol diglycidyl ether; and modified versions thereof. These bifunctional epoxy compounds may be used individually or in combination of two or more. Among them, bifunctional alicyclic epoxy resins such as dicyclopentadiene dimethanol diglycidyl ether and polyalkylene glycol diglycidyl ethers such as polypropylene glycol diglycidyl ether are preferred from the viewpoint of reactivity and workability.

[0052] Examples of the above-mentioned epoxy compounds with three or more functions include three or more aromatic epoxy resins such as three or more phenol novolac type epoxy resins, three or more alicyclic epoxy resins, three or more glycidyl ester type epoxy resins, three or more glycidylamine type epoxy resins such as tetraglycidyldiaminodiphenylmethane, triglycidyl-p-aminophenylmethane, triglycidyl-m-aminophenylmethane, and tetraglycidyl-m-xylylenediamine, three or more heterocyclic epoxy resins, three or more diarylsulfone type epoxy resins, three or more alkylene glycidyl ether compounds such as glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether, three or more glycidyl group-containing hydantoin compounds, three or more glycidyl group-containing siloxanes, and modified products thereof. These three or more epoxy resins may be used alone or in combination of two or more.

[0053] In the carbon fiber reinforced composite material of the present invention, the content of the epoxy resin is preferably 3% by weight at the lower limit, more preferably 6.5% by weight at the lower limit, preferably 66% by weight at the upper limit, and more preferably 56% by weight at the upper limit.

[0054] The epoxy resin described above has a preferred lower limit of 100 and a preferred upper limit of 5000 in epoxy equivalent (molecular weight per epoxy group). The molecular weight of the epoxy resin described above has a preferred lower limit of 100 and a preferred upper limit of 70,000.

[0055] In the carbon fiber reinforced composite material of the present invention, the ratio of the polyvinyl acetal resin content to the epoxy resin content (polyvinyl acetal resin content / epoxy resin content) is preferably 0.0001 as the lower limit, more preferably 0.001 as the lower limit, preferably 0.4 as the upper limit, and more preferably 0.35 as the upper limit.

[0056] The carbon fiber reinforced composite material of the present invention contains a curing agent. Examples of the curing agents mentioned above include phenolic curing agents, thiol curing agents, amine curing agents, imidazole curing agents, acid anhydride curing agents, cyanate curing agents, and active ester curing agents. Among these, amine curing agents are preferred. Furthermore, the curing agent is preferably a nitrogen-containing compound.

[0057] Examples of the amine-based curing agents mentioned above include trimethylamine, triethylamine, N,N-dimethylpiperazine, triethylenediamine, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4.0)-undecene-7, and 1,5-diazabicyclo(4,3.0)-nonene-5.

[0058] Examples of the imidazole-based curing agents mentioned above include imidazole, 2-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzylimidazole, 1-benzyl-2-phenylimidazole, and 1-cyanoethyl-2-methylimidazole.

[0059] The content of the curing agent in the carbon fiber reinforced composite material of the present invention is preferably 0.5 parts by weight, more preferably 1.0 part by weight, preferably 100 parts by weight, and more preferably 50 parts by weight per 100 parts by weight of the epoxy resin. Furthermore, the content of the above-mentioned curing agent in the carbon fiber reinforced composite material of the present invention is preferably 0.015 to 70% by weight.

[0060] The carbon fiber reinforced composite material of the present invention may further contain a curing accelerator and an organic solvent. Examples of the curing accelerators mentioned above include phosphorus compounds, amine compounds, and organometallic compounds. The content of the curing accelerator in the carbon fiber reinforced composite material of the present invention is preferably 0.1 parts by weight, more preferably 0.5 parts by weight, preferably 30 parts by weight, and more preferably 10 parts by weight per 100 parts by weight of the epoxy resin.

[0061] Examples of the above-mentioned organic solvents include ketones, alcohols, aromatic hydrocarbons, and esters. Examples of the above-mentioned ketones include acetone, methyl ethyl ketone, dipropyl ketone, and diisobutyl ketone. Examples of the above-mentioned alcohols include methanol, ethanol, isopropanol, and butanol. Examples of the above-mentioned aromatic hydrocarbons include toluene and xylene. Examples of the above esters include methyl propionate, ethyl propionate, butyl propionate, methyl butanoate, ethyl butanoate, butyl butanoate, methyl pentanoate, ethyl pentanoate, butyl pentanoate, methyl hexanoate, ethyl hexanoate, butyl hexanoate, 2-ethylhexyl acetate, and 2-ethylhexyl butyrate. In addition, methyl cellsolve, ethyl cellsolve, butyl cellsolve, terpineol, dihydroterpineol, butyl cellsolve acetate, butyl carbitol acetate, terpineol acetate, dihydroterpineol acetate, etc. can also be used.

[0062] The content of the above-mentioned organic solvent in the carbon fiber reinforced composite material of the present invention preferably has an upper limit of 5.0% by weight, and is particularly preferably 0% by weight.

[0063] The carbon fiber reinforced composite material of the present invention may contain other resins such as acrylic resin and ethyl cellulose, as long as the effects of the present invention are not impaired. In such cases, it is preferable that the content of the other resin is 10% by weight or less.

[0064] The carbon fiber reinforced composite material of the present invention may further contain known additives such as tackifying resins, adhesion modifiers, emulsifiers, antioxidants, softeners, fillers, pigments, dyes, silane coupling agents, antioxidants, surfactants, and waxes, to the extent that they do not impair the effects of the present invention.

[0065] The method for producing the carbon fiber reinforced composite material of the present invention is not particularly limited, and for example, it may include at least the steps of: preparing a resin composition containing an epoxy resin, a curing agent, and a polyvinyl acetal resin; and compounding the resin composition with carbon fibers, wherein the polyvinyl acetal resin contains the constituent units shown in formula (1), and R in formula (1) 1 A method for producing carbon fiber reinforced composite materials can be used, in which the alkyl group has one or more carbon atoms. Furthermore, regarding the epoxy resin, curing agent, and polyvinyl acetal resin components in the method for producing the carbon fiber reinforced composite material of the present invention, as well as the constituent units of the polyvinyl acetal resin shown in formula (1) above, these are the same as in the case of the carbon fiber reinforced composite material of the present invention, and therefore their explanation is omitted.

[0066] The process for producing the above-mentioned resin composition includes mixing the epoxy resin, curing agent, polyvinyl acetal resin, and various additives as needed using various mixing machines such as ball mills, blender mills, three-roll mixers, dispensers, and planetary mixers. Furthermore, the resin composition may be prepared by mixing the epoxy resin and the polyvinyl acetal resin and then adding a curing agent, or by adding the epoxy resin, curing agent, and polyvinyl acetal resin simultaneously.

[0067] Methods for compounding the above resin composition with carbon fibers include, for example, impregnation of the carbon fibers. Specifically, examples include the autoclave method, press method, hand lay-up method, pultrusion method, filament winding method, RTM method, pin winding method, infusion method, hot (cold) press method, spray-up method, and continuous press method.

[0068] The applications of carbon fiber reinforced composite materials are not particularly limited and can be used in a variety of applications, including aircraft structural materials, automotive, marine, sports equipment, and other general industrial applications such as wind turbines and rollers. However, their application is particularly preferred when prepregs are used as intermediate components. [Effects of the Invention]

[0069] According to the present invention, it is possible to provide a carbon fiber reinforced composite material and a method for producing a carbon fiber reinforced composite material that have excellent tackiness, compatibility with epoxy resins and interfacial adhesion, as well as high mechanical strength. [Modes for carrying out the invention]

[0070] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0071] (Example 1) (Preparation of polyvinyl acetal resin) 250 g of polyvinyl alcohol resin with an average degree of polymerization of 300 and a degree of saponification of 99 mol% was added to 2700 g of pure water and stirred at 90°C for about 2 hours to dissolve. This solution was cooled to 40°C, and 100 g of hydrochloric acid with a concentration of 35 wt% and 90 g of acetaldehyde were added to carry out the acetalization reaction, and the reaction product was precipitated. Subsequently, the acetalization reaction was completed at 40°C, and neutralization, washing with water, and drying were performed by conventional methods to obtain a white powder of polyvinyl acetal resin. The obtained polyvinyl acetal resin is dissolved in DMSO-d6 at a concentration of 10% by weight. 13 The amount of alkyl acetal groups (degree of acetacetalization), hydroxyl groups, and acetyl groups was measured using 1C-NMR.

[0072] (Fabrication of carbon fiber reinforced composite materials [prepregs]) To 100 parts by weight of bisphenol A type epoxy resin (JER828, manufactured by Japan Epoxy Resin Co., Ltd.), 6 parts by weight of a curing agent (dicyandiamide) and 10 parts by weight of the resulting polyvinyl acetal resin were added and mixed at 15,000 rpm using a process homogenizer (manufactured by SMT Co., Ltd.) to prepare the resin composition. Subsequently, the obtained resin composition was laid up using a hand lay-up method with PAN-based carbon fibers (Toray Industries, Ltd., T700SC-12000-50C, filament count: 12000, fineness: 800 tex, density: 1.8 g / cm³). 3 The prepreg was prepared by impregnating the material with ( ) and curing it by heating at 150°C for 1 hour. In this case, 300 parts by weight of PAN-based carbon fiber was used for every 100 parts by weight of bisphenol A type epoxy resin.

[0073] (Examples 2-10, 17, 19-21, Comparative Examples 1-4) Polyvinyl acetal resin, resin composition, and prepreg were prepared in the same manner as in Example 1, except that the types and amounts of polyvinyl alcohol resin (PVA) and aldehydes shown in Table 1 were used, and the resin composition was prepared with the composition shown in Table 2. Note that the polyvinyl acetal resins obtained in Examples 1 and 2, and Examples 4 and 5 are the same. Furthermore, in Examples 4-6, 8, and Comparative Example 3, two different aldehydes were used. Furthermore, in Example 17 and Comparative Example 4, bisphenol F type epoxy resin (NPEF-170, manufactured by Nanya Plastics Co., Ltd.) was used instead of bisphenol A type epoxy resin (JER828, manufactured by Japan Epoxy Resin Co., Ltd.).

[0074] (Example 11) (Preparation of carboxylic acid-modified polyvinyl acetal resin) 100 g of carboxylic acid-modified polyvinyl alcohol resin was added to 1000 g of pure water and stirred at 90°C for approximately 2 hours to dissolve. This solution was cooled to 40°C, and 90 g of hydrochloric acid (35% by weight) and 90 g of acetaldehyde were added to the solution. The solution temperature was lowered to 10°C and maintained at this temperature to carry out the acetalization reaction. After that, the reaction was maintained at 40°C for 3 hours to complete, and neutralization, washing with water, and drying were performed by conventional methods to obtain a white powder of carboxylic acid-modified polyvinyl acetal resin. Furthermore, carboxylic acid-modified polyvinyl alcohol resin is a constituent unit having a carboxyl group represented by formula (4-1) (in formula (4-1), R 2 is a single bond, R 3 is a methylene group, X 1 , X 2 It has a hydrogen atom, an average degree of polymerization of 400, a degree of saponification of 99.0 mol%, and an acid-modified group content of 0.7 mol%. Here, the single bond refers to an alkylene group with 0 carbon atoms. Resin compositions and prepregs were prepared in the same manner as in Example 1, except that the obtained carboxylic acid-modified polyvinyl acetal resin was used.

[0075] (Example 12) In the "Preparation of Carbon Fiber Reinforced Composite Materials [Prepregs]," a carboxylic acid-modified polyvinyl acetal resin, a resin composition, and a prepreg were prepared in the same manner as in Example 11, except that the amount of polyvinyl acetal resin added was 2 parts by weight.

[0076] (Example 13) As a carboxylic acid-modified polyvinyl alcohol resin, a constituent unit having a carboxyl group represented by formula (4-1) (in formula (4-1), R 2 is a single bond, R 3 is a methylene group, X 1 , X 2 Carboxylic acid-modified polyvinyl acetal resin, resin composition, and prepreg were prepared in the same manner as in Example 11, except that a material was used that had a hydrogen atom, an average degree of polymerization of 400, a degree of saponification of 99.0 mol%, and an acid-modified group content of 2.0 mol%.

[0077] (Example 14) As a carboxylic acid-modified polyvinyl alcohol resin, a constituent unit having a carboxyl group represented by formula (4-1) (in formula (4-1), R 2 is a single bond, R 3 is a methylene group, X 1 , X 2 A carboxylic acid-modified polyvinyl acetal resin, resin composition, and prepreg were prepared in the same manner as in Example 11, except that a material having hydrogen atoms, an average degree of polymerization of 600, a degree of saponification of 99.0 mol%, and an acid-modified group content of 1.0 mol%, was used, and the amount of acetaldehyde added was 110 g.

[0078] (Example 15) (Preparation of sulfonic acid-modified polyvinyl acetal resin) 100 g of sulfonic acid-modified polyvinyl alcohol resin was added to 1000 g of pure water and stirred at 90°C for approximately 2 hours to dissolve. This solution was cooled to 40°C, and 90 g of hydrochloric acid (35% by weight) and 90 g of acetaldehyde were added to the solution. The solution temperature was lowered to 10°C and maintained at this temperature to carry out the acetalization reaction. After that, the reaction was maintained at 40°C for 3 hours to complete, and neutralization, washing with water, and drying were performed by conventional methods to obtain a white powder of sulfonic acid-modified polyvinyl acetal resin. The sulfonic acid-modified polyvinyl alcohol resin has a structure in which the sulfonic acid group is directly bonded to the carbon atoms of the main chain, with an average degree of polymerization of 300, a degree of saponification of 99.0 mol%, and an acid-modified group content of 0.7 mol%. Resin compositions and prepregs were prepared in the same manner as in Example 1, except that the obtained sulfonic acid-modified polyvinyl acetal resin was used.

[0079] (Example 16) As a carboxylic acid-modified polyvinyl alcohol resin, a constituent unit having a carboxyl group represented by formula (4-1) (in formula (4-1), R 2 is a single bond, R 3 is a methylene group, X 1 , X 2A carboxylic acid-modified polyvinyl acetal resin, resin composition, and prepreg were prepared in the same manner as in Example 11, except that a material having hydrogen atoms, an average degree of polymerization of 2500, a degree of saponification of 99.0 mol%, and an acid-modified group content of 1.0 mol%, was used, and 38 g of acetaldehyde and 110 g of butyraldehyde were added instead of 90 g of acetaldehyde.

[0080] (Example 18) In the "Preparation of Carbon Fiber Reinforced Composite Materials [Prepregs]," carboxylic acid-modified polyvinyl acetal resin, resin compositions, and prepregs were prepared in the same manner as in Example 11, except that bisphenol F type epoxy resin (NPEF-170, manufactured by Nanya Plastics Co., Ltd.) was used instead of bisphenol A type epoxy resin (JER828, manufactured by Japan Epoxy Resin Co., Ltd.).

[0081] (evaluation) The polyvinyl acetal resins, resin compositions, and prepregs obtained in the examples and comparative examples were evaluated as follows. The results are shown in Tables 1 and 2.

[0082] (1) Measurement of glass transition temperature (Tg) The glass transition temperature of the obtained polyvinyl acetal resin was measured using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min.

[0083] (2) Tensile strain The obtained resin composition was cured by heating at 150°C for 1 hour to produce a resin-cured plate. Dumbbell test specimens (JIS K7161-2-1B type) were cut from this plate, and the tensile strain was measured using a universal testing machine (Instron) under the following conditions. Test conditions: JIS K 7161-2 Test speed: 1 mm / min Gap distance: 115mm Furthermore, if the tensile strain of the resin composition is high, a similarly high tensile strain can be achieved even when using a prepreg.

[0084] (3) Compatibility with epoxy resins An evaluation sample was prepared by adding 10 parts by weight of the obtained polyvinyl acetal resin to 90 parts by weight of the epoxy resin used in "Preparation of carbon fiber reinforced composite material [prepreg]" and heating and melting it at 150°C. The prepared samples were allowed to cool to room temperature and left to stand at room temperature for 24 hours. During this process, the appearance was observed at three points: "at 150°C," "at 70°C during cooling," and "after standing at room temperature for 24 hours." The presence or absence of phase separation was checked based on whether the sample was clear or cloudy, and it was evaluated according to the following criteria. ◎: Good compatibility at 150℃, 70℃, and room temperature; the solution is transparent. ○: No phase separation occurs at 150℃ and 70℃, but the solution is cloudy at room temperature. △: No phase separation occurs at 150℃, but the solution becomes cloudy at 70℃ and room temperature. ×: Does not dissolve at 150℃, solution is cloudy.

[0085] (4) Adhesion (measurement of interfacial shear strength) Resin compositions containing polyvinyl acetal obtained in the examples and comparative examples were dropped onto carbon fibers and cured by heating at 150°C for 1 hour to prepare measurement samples. The interfacial shear strength between the carbon fibers and the resin of the prepared samples was measured using a composite material interface property evaluation device (HM410, manufactured by Toei Sangyo Co., Ltd.) by the microdroplet method (drawout speed: 0.12 mm / min).

[0086] (5) Toughness After stacking five sheets of the obtained prepreg, holes were drilled, and the openings were visually inspected and evaluated according to the following criteria. ◎: No delamination has occurred at all. ○: Only one sheet peeled off. ×: Two or more layers have peeled off.

[0087] (6) Tuck The tackiness of the obtained prepregs was evaluated by touch according to the following criteria. ◎: Appropriate tackiness and excellent handling. ○: There is some slight excess or deficiency in the tuck, but there are no problems with handling. ×: The tackiness is either excessive or significantly insufficient, resulting in handling problems.

[0088] [Table 1]

[0089] [Table 2] [Industrial applicability]

[0090] According to the present invention, it is possible to provide a carbon fiber reinforced composite material that has excellent tackiness, compatibility with epoxy resins, and interfacial adhesion, while also achieving high mechanical strength.

Claims

1. A carbon fiber reinforced composite material containing carbon fiber, epoxy resin, curing agent, and polyvinyl acetal resin, The polyvinyl acetal resin contains the constituent units shown in the following formula (1): R in equation (1) below 1 is an alkyl group having 1 or more carbon atoms and containing at least one methyl group, It contains a constituent unit having at least one acid-modified group selected from the group consisting of the constituent unit represented by the following formula (4-1), the constituent unit represented by the following formula (4-2), and the constituent unit represented by the following formula (4-3), The hydroxyl group content is 16.0 mol% or more and 45.0 mol% or less. The glass transition temperature is 75°C or higher. Carbon fiber reinforced composite material. 【Chemistry 1】 In formula (1), R 1 These may be the same or they may be different. 【Chemistry 2】 In formula (4-1) above, R2 and R3 each independently represent an alkylene group having 0 to 10 carbon atoms, and X1 and X2 each independently represent a hydrogen atom, a metal atom, or a methyl group. In formula (4-2) above, R4, R5, and R6 each independently represent a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, R7 represents an alkylene group having 0 to 10 carbon atoms, and X3 represents a hydrogen atom, a metal atom, or a methyl group. Note that when R2, R3, or R7 is an alkylene group having 0 carbon atoms, it means that R2, R3, or R7 is a single bond. In formula (4-3) above, R8 represents an alkylene group having 0 to 10 carbon atoms, and X4 represents a hydrogen atom, a metal atom, or a methyl group. Note that a carbon number of 0 means that there is no alkylene group, that is, it means that there is no alkylene group and it is directly bonded.

2. Polyvinyl acetal resin contains R in formula (1). 1 The carbon fiber reinforced composite material according to claim 1, wherein the alkyl group has one or more carbon atoms and contains at least one methyl group, and the alkyl group has three or more carbon atoms.

3. The carbon fiber reinforced composite material according to claim 1 or 2, wherein the polyvinyl acetal resin has an average degree of polymerization of 2500 or less.

4. The carbon fiber reinforced composite material according to claim 1 or 2, wherein the polyvinyl acetal resin contains 0.01 to 20 mol% of constituent units having acid-modified groups.

5. The carbon fiber reinforced composite material according to claim 1 or 2, wherein the polyvinyl acetal resin content is 0.01 parts by weight or more and 40.0 parts by weight or less per 100 parts by weight of epoxy resin.

6. A process for preparing a resin composition containing epoxy resin, a curing agent, and polyvinyl acetal resin, The process includes at least the step of compounding the resin composition with carbon fibers, The polyvinyl acetal resin contains the constituent units shown in the following formula (1): R in equation (1) below 1 is an alkyl group having 1 or more carbon atoms and containing at least one methyl group, It contains a constituent unit having at least one acid-modified group selected from the group consisting of the constituent unit represented by the following formula (4-1), the constituent unit represented by the following formula (4-2), and the constituent unit represented by the following formula (4-3), The hydroxyl group content is 16.0 mol% or more and 45.0 mol% or less. The glass transition temperature is 75°C or higher. A method for manufacturing carbon fiber reinforced composite materials. 【Transformation 3】 In formula (1), R 1 These may be the same or they may be different. 【Chemistry 4】 In formula (4-1) above, R2 and R3 each independently represent an alkylene group having 0 to 10 carbon atoms, and X1 and X2 each independently represent a hydrogen atom, a metal atom, or a methyl group. In formula (4-2) above, R4, R5, and R6 each independently represent a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, R7 represents an alkylene group having 0 to 10 carbon atoms, and X3 represents a hydrogen atom, a metal atom, or a methyl group. Note that when R2, R3, or R7 is an alkylene group having 0 carbon atoms, it means that R2, R3, or R7 is a single bond. In formula (4-3) above, R8 represents an alkylene group having 0 to 10 carbon atoms, and X4 represents a hydrogen atom, a metal atom, or a methyl group. Note that a carbon number of 0 means that there is no alkylene group, that is, it means that there is no alkylene group and it is directly bonded.

Citation Information

Patent Citations

  • Epoxy resin composition and prepreg

    JP1993186667A

  • prepreg

    JP1994009802A

  • Epoxy resin composition and prepreg containing the same

    JP2006335791A

  • Prepreg and fiber-reinforced composite material using same

    WO2019202762A1